Developmental and Morphological Indices of Phaseolus vulgaris L. and Soil Physico-chemical Properties during Serial Flooding in Bayelsa State, Nigeria - M. Etukudo , Mbosowo; Onu, Benefit (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
Background: Flooded soil is a significant agronomic problem because most plants do not tolerate excess water in the soil. Yenagoa, Bayelsa State is characterized by seasonal flooding that often engulf cultivated soils This study was conducted to assess the response of Phaseolus vulgaris to flooded soil condition in the study area. Methods: Viable seeds of the test crop were sterilized and sown in soils of Site A (control) and B (flooded soil) in rows. The research work was planned such that, the P. vulgaris seedlings were established up to one (1) month before the area (Site B) was flooded. Plant growth parameters such as plant height, leaf number, dry weight, nitrogen, phosphorus and potassium contents were examined. Standard methods were used to determine the mineral nutrient compositions in the test plant. Soil physico-chemical properties of the experimental soils were determined. Results: P. vulgaris exhibited moderate wilting and chlorosis during the first week of exposure to flood condition. The severity of wilting and chlorosis increased with increase in the duration of the stress condition. Other morphological characteristics observed were retarded growth, dropping of leaves, decrease leaf number, and reduced leaf size during the second and third week of exposure to flood condition, and death of the entire plant at the fourth week of study. There were significant (P< 0.05) reductions in nitrogen, phosphorus and potassium contents of P. vulgaris under flooded condition relative to the control Conclusion: This study showed that P. vulgaris was susceptible to flooded soil.